Corpus luteum presence in the bovine ovary increase intrafollicular progesterone concentration: consequences in follicular cells gene expression and follicular fluid small extracellular vesicles miRNA contents - Paola Maria da Silva Rosa; Alessandra Bridi; Giuliana de Ávila Ferronato; Cibele Maria Prado; Natália Marins Bastos; Juliano Rodrigues Sangalli; Flávio Vieira Meirelles; Felipe Perecin; Juliano Coelho da Silveira (BMC, 2024)
Abstract Background It is well described that circulating progesterone (P4) plays a key role in several reproductive events such as oocyte maturation. However, during diestrus, when circulating P4 is at the highest concentrations, little is known about its local impact on the follicular cells such as intrafollicular P4 concentration due to corpus luteum (CL) presence within the same ovary. Based on that, our hypothesis is that the CL presence in the ovary during diestrus alters intrafollicular P4 concentrations, oocyte competence acquisition, follicular cells gene expression, and small extracellular vesicles (sEVs) miRNAs contents. Results P4 hormonal analysis revealed that ipsilateral to the CL follicular fluid (iFF) presented higher P4 concentration compared to contralateral follicular fluid (cFF). Furthermore, oocyte maturation and miRNA biogenesis pathways transcripts (ADAMTS-1 and AGO2, respectively) were increased in cumulus and granulosa cells of iFF, respectively. Nevertheless, a RT-PCR screening of 382 miRNAs showed that three miRNAs were upregulated and two exclusively expressed in sEVs from iFF and are predicted to regulate cell communication pathways. Similarly, seven miRNAs were higher and two exclusively expressed from cFF sEVs and are predicted to modulate proliferation signaling pathways. Conclusion In conclusion, intrafollicular P4 concentration is influenced by the presence of the CL and modulates biological processes related to follicular cell development and oocyte competence, which may influence the oocyte quality. Altogether, these results are crucial to improve our knowledge about the follicular microenvironment involved in oocyte competence acquisition.